Efektifitas Model Pembelajaran Jigsaw Berbasis Permainan Puzzle Untuk Meningkatkan Kemampuan Qira’ah di SMP Takhasus Al Qur’an Wonosobo - Rahmiati Rahmiati; Asep Sunarko; Ahmad Rois (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2022)
Maharah Qira'ah learning at Takhasus Al Qur'an Middle School uses a conventional learning model. There are many students who are passive when learning takes place, and lack participation, and the majority of students think learning Arabic is difficult. so it is necessary to apply a varied and enjoyable learning model. The use of a jigsaw learning model based on puzzle games is expected to be the solution. This study uses an experimental model that uses a one-group pretest-posttest design. The study used the subject of class VII students of SMP Takhasus Al Qur'an, totaling 63 students divided into two groups: control and experimental groups, then the experimental and control groups were subjected to a pretest and a final test in the form of written questions at the end (posttest). ). The research results will be analyzed, processed, and compared using the t-test and the N-Gain score test to obtain differences and increase in maharah qira'ah on research subjects. The results of this study indicate that: 1) in learning maharah qira'ah at Takhasus Al Qur'an Middle School using a jigsaw model based on a puzzle game there are steps that are used when learning takes place; 2) there is an increase in the qira'ah maharah of experimental class students by 0.51 which is included in the medium category; 3) there is a difference between the experimental class and the control class with tcount 5,19 > ttable1,671. So that Ha can be accepted and Ho can be rejected.